The Potentials of Improving Mineral Source Additional Values in Lampung Province – A Prelimanary Study - K Isnugroho; D C Birawidha; M Amin (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2019)
An initial research on non-metal mineral potential was conducted for stones in Lampung Province. Surveys were conducted to some districts/towns in Lampung to take sample materials. Non-metal mineral chemical composition content analysis of stones was conducted with X-RF method. Lampung had mineral potentials of feldspar, zeolite, kaolin, and basalt of 400,500,000 m3; 18,945,000 m3; 9,750,000 m3; 419,071,833 m3 respectively. These mineral source potentials were distributed in eight districts in Lampung. Processing was required to improve additional values for these mineral sources, including crushing, grinding, classifying, and concentration process. Concentration improvements were required for feldspar and kaolin minerals. Wet high intensity magnetic separator process followed by froth flotation process became solutions to reduce high oxide iron content. Feldspar and kaolin could be used for such industries of ceramic, glass, paper, and refractory. Meanwhile, the zeolite mineral from Lampung could be used for agriculture, plantation, and fishery. Basalt stone would have additional values when this was processed into cast basalt, fiber, and ceramic composite.